2016
DOI: 10.3347/kjp.2016.54.4.497
|View full text |Cite
|
Sign up to set email alerts
|

Pygidiopsis summa (Digenea: Heterophyidae): Status of Metacercarial Infection in Mullets from Coastal Areas in the Republic of Korea

Abstract: To know the infection status of zoonotic trematode metacercariae in brackish water fish, we surveyed mullets collected from 18 coastal areas in the Republic of Korea. The metacercariae of Pygidiopsis summa were detected in 236 (68.2%) out of 346 mullets examined. They were found in mullets from 15 areas except for those from Boseong-gun (Jeollanam-do), Pohang-si, and Uljin-gun (Gyeongsangbuk-do). Especially in mullets from Taean-gun (Chungcheongnam-do) and Geoje-si (Gyeongsangnam-do), their prevalences were 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Guk et al [28] found total 8 PsMc in only one mullet from Donghae-si, Gangwon-do, and they could not detect PsMc at all in mullet from Yeongdeok-gun, Gyeongsangbuk-do, and Sokcho-si, Gangwon-do. In Sohn et al [29], PsMc were detected in 38 (63.3%) out of 60 mullet from 5 eastern coastal sites, i.e., Ulsan Metropolitan City, Yeongdeokgun, Gyeongsangbuk-do, and Gangneung-si, 2 sites in Goseong-gun, Gangwon-do, but they were not found in 29 mullet from Pohang-si and Uljin-gun, Gyeongsangbuk-do. However, in the present study, P. summa metacercariae (PsMc) were found in 48 (84.2%) out of 57 mullets examined, and their density was 316 per fish infected.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Guk et al [28] found total 8 PsMc in only one mullet from Donghae-si, Gangwon-do, and they could not detect PsMc at all in mullet from Yeongdeok-gun, Gyeongsangbuk-do, and Sokcho-si, Gangwon-do. In Sohn et al [29], PsMc were detected in 38 (63.3%) out of 60 mullet from 5 eastern coastal sites, i.e., Ulsan Metropolitan City, Yeongdeokgun, Gyeongsangbuk-do, and Gangneung-si, 2 sites in Goseong-gun, Gangwon-do, but they were not found in 29 mullet from Pohang-si and Uljin-gun, Gyeongsangbuk-do. However, in the present study, P. summa metacercariae (PsMc) were found in 48 (84.2%) out of 57 mullets examined, and their density was 316 per fish infected.…”
Section: Discussionmentioning
confidence: 90%
“…They reported 87.0%, 54.1%, and 4.0% PsMc prevalences and 177, 47, and 8 PsMc densities in mullet from coastal areas of Yellow Sea, South Sea and East Sea respectively. Recently, Sohn et al [29] also reported 93.8%, 69.3%, and 42.7% PsMc prevalences, and 496, 369, and 291 PsMc densities in mullets from the coastal areas of upper 3 Seas respectively. From the 2 studies aforementioned, we can know that the endemicity of PsMc in mullet from eastern coastal areas is much lower than those in mullet from southern and western coastal areas of Korea.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, Cho et al [ 26 ] surveyed the infection status of trematode metacercariae in estuarine fishes including yellowfin goby from Muan-gun, Jeollanam-do. Sohn et al [ 27 ] investigated the infection status of P. summa metacercariae in mullets from coastal areas of Korea. However, most of studies were performed in limited areas and the number of fish was not enough to evaluate the metacercarial endemicity in each surveyed area.…”
Section: Introductionmentioning
confidence: 99%